Transtorno do Espectro Autista na Educação Infantil: bases legais, políticas e subsídios teóricos - Silva, Jéssica Vinente da (Brasil, 2025)
The main objective of this study was to analyze the legal documents that guarantee the inclusion of people with Autism Spectrum Disorder (ASD) in regular schools in the city of Manaus/AM, covering the international, federal and municipal levels. To achieve this goal, the following specific objectives were defined: a bibliographic and documentary survey, an analysis of the documents and a discussion of the challenges encountered in the process of including individuals with ASD. As a result, the main documents and laws related to educational policies for the inclusion of Special Education students, at the international, federal and municipal levels, in force to date, were compiled. The analysis of the data allowed us to understand the impact of the creation of public policies on expanding access and services that ensure the permanence of Special Education students in schools in the Municipal Education Network of Manaus/AM.